Memórias do isolamento: trajetórias marcadas pela experiência de vida no Hospital Colônia Itapuã - Serres, Juliane Conceição Primon (Universidade do Vale do Rio do Sinos, 2009)
The present theses analyses the experience of having leprosy in Rio Grande do Sul and being isolated in the Colony Hospital Itapuã. We aimed at discussing the processes of isolation, exclusion and rebuilding of life inside the institution. Founded in the 1940’s the leprosarium isolated inflicted people from all over the state. Some of them still live in the hospital and through their story we were able to capture their experience. It was also possible to contact people who left the leprosarium and through those two distinct paths we analyzed the medical and social struggle that meant a leprosy diagnosis only a few decades ago. Lori and GM are the main characters of that plot. She is the oldest resident in Itapuã and her personal story is deeply connected to the institution’s; he was admitted in the 1940’s but has lived outside the hospital for over 50 years, and his life has been enormously affected by the time he spent there and the living with that memory. The focus on those two individual micro universes h
Memories of isolation: trajectories marked by the experience of life in the Colony Hospital Itapuã
Keywords: experiência; isolamento; lepra; experience; isolation; leprosy; Ciências Humanas